2017
DOI: 10.1111/phpp.12280
|View full text |Cite
|
Sign up to set email alerts
|

Skin microtopography as a measure of photoaging and risk of squamous cell carcinoma of the skin in a US population

Abstract: Background Skin microtopography as a measure of photoaging is a non-invasive approach to measuring chronic ultraviolet radiation (UVR) exposure, and reflects the degree of dermal elastosis in populations of European descent in the subtropics. Less is known about the utility of this approach in populations at different latitudes, and whether it relates to skin cancer risk. Methods A population-based case-control study of 342 SCC cases and 331 age- and gender-matched controls were evaluated for histologic evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Similar proportions of cases (36%) and controls (34%) consented to participate. Host factors were self‐reported, as in many studies, as were solar keratoses; we found the latter influenced skin cancer risk in NSW similarly to other high and low ambient UV environments. Individual past sun exposure is almost impossible to measure accurately .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar proportions of cases (36%) and controls (34%) consented to participate. Host factors were self‐reported, as in many studies, as were solar keratoses; we found the latter influenced skin cancer risk in NSW similarly to other high and low ambient UV environments. Individual past sun exposure is almost impossible to measure accurately .…”
Section: Discussionsupporting
confidence: 63%
“…) than in New Hampshire (30%; Ref. ) or readily develop a tan (Australia 30–36%; Ref. ) than in the US Nurses Health Study (14%; Ref.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that individuals who are often exposed to the sun, such as construction workers, farmers, sailors, and truck drivers, frequently suffer from severe effects of UVR over a lifetime 34, 35 . For these individuals, apart from taking other preventive measures, 36 regular monitoring of sun‐exposed skin by OCT could be meaningful and prevent the development of skin cancer, such as cSCC 37, 38 . Once the typical shape of the DEJ and a continuous increase in epidermal thickness are found, this may indicate that the skin is undergoing AK.…”
Section: Resultsmentioning
confidence: 99%
“…The study dermatopathologist confirmed all cuSCC diagnoses and graded the degree of solar elastosis present in the adjacent normal tissue, a measure of cumulative UVR (30). Solar elastosis was graded on a 4-point scale: 0: no presence of elastotic fibers or very occasional elastotic fibers; 1: scattered elastotic fibers lying as individual units between collagen bundles; 2: densely scattered elastotic fibers distributed predominantly as bushels rather than individual units; 3: dense aggregates of elastotic fibers forming amorphous deposits of blue-gray material with lost fiber texture (33)(34)(35).…”
Section: Measurement Of T-regulatory Cells and Solar Elastosis In Tumor Tissuesmentioning
confidence: 99%